2006
DOI: 10.1021/bi060839c
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Fosfomycin, Re-Examination and Re-Confirmation of a Unique Fe(II)- and NAD(P)H-Dependent Epoxidation Reaction

Abstract: Abstract(S)-2-hydroxypropylphosphonic acid epoxidase (HppE) catalyzes the epoxide ring closure of (S)-HPP to form fosfomycin, a clinically useful antibiotic. Early investigation showed that its activity can be reconstituted with Fe(II), FMN, NADH, and O 2 , and identified HppE as a new type of mononuclear non-heme iron-dependent oxygenase involving high valent iron-oxo species in the catalysis. However, a recent study showed that the Zn(II)-reconstituted HppE is active, and HppE exhibits modest affinity for FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Further analysis revealed that Zn 2ϩ strongly inhibited LipL activity (supplemental Fig. S12), and therefore co-purification with Zn 2ϩ is likely due to adventitious binding as observed with other non-heme, iron-dependent oxygenases (28). Inhibition by divalent transition metals has been reported for TauD (16) and clavaminic acid synthase (29).…”
Section: Resultsmentioning
confidence: 76%
“…Further analysis revealed that Zn 2ϩ strongly inhibited LipL activity (supplemental Fig. S12), and therefore co-purification with Zn 2ϩ is likely due to adventitious binding as observed with other non-heme, iron-dependent oxygenases (28). Inhibition by divalent transition metals has been reported for TauD (16) and clavaminic acid synthase (29).…”
Section: Resultsmentioning
confidence: 76%
“…Fosfomycin (cis-(1R,2S)-epoxypropylphosphonic acid) is an oxirane antibiotic unrelated to other substances and is produced as a secondary metabolite by Streptomyces and Pseudomonas spp [14]. (S)-2-hydroxypropylphosphonic acid epoxidase catalyzes the epoxide ring closure of (S)-2-hydroxypropylphosphonic acid to form fosfomycin in an iron-redox mechanism [34]. Hydroxypropylphosphonic acid epoxidase represents a new subfamily of non-haem mononuclear iron enzymes that respond to its substrates with a conformational change that protects the radical-based intermediates formed during catalysis [35].…”
Section: Fosfomycinmentioning
confidence: 99%
“…The crude products were purified by flash silica gel column chromatography with hexanes/ethyl acetate (10:1 to 1:1) to give diethyl isobutylphosphonate (11) in 90% yield. A portion of 11 (0.5 g, 2.6 mmol) was then incubated with trimethylsilyl bromide (TMSBr, 0.5 mL, 3.8 mmol) and allyltrimethylsilane (0.25 mL, 1.6 mmol) for 24 h at room temperature.…”
Section: Synthesis Of Isobutylphosphonic Acid (Ibp 9) (Scheme 2)mentioning
confidence: 99%
“…The purified HppE, after reconstitution, contains a mononuclear non-heme iron that is essential and cannot be replaced by other divalent ions (10,11). The in vitro activity of HppE also requires NAD(P)H, dioxygen, and an auxiliary electron mediator to transfer electrons from NAD(P)H to the enzyme active site (8,9,11). While this mediator's role can be fulfilled by small molecule electron carriers, such as FMN, FAD, riboflavin, and benzyl viologen (11), the physiological mediator is expected to be a reductase, which has not yet been identified.…”
mentioning
confidence: 99%